The Role of Public Spending and The Quality of Public Services in E-government Development - Ibrahim Niftiyev (Materials II International Conference “Digital Economy: Modern Challenges and Real Opportunities”, 28 - 29 April 2022, 2022)
Numerous studies have concluded that trends in e-government development have spread throughout the world economy and that public sector performance is a significant determinant of this process. Moreover, an expansion in the available literature and data sources also present additional incentives to pursue new studies on changing patterns in e-government development. The current paper analyzes the association between e-government development (using the E-Government Development Index or EGDI as a proxy), government spending, and the quality of public services against the background of economic and population growth in 154 countries. The results met the assumption that economic growth (represented by GDP per capita), government effectiveness, and the Public Services Index would positively impact EGDI. However, government spending had a negative impact on EGDI index between 2008 and 2018, which potentially indicates inefficiencies in government expenditures on e-government development.
Keywords: 330; panel least squares; public services; random effects; E-Government Development Index (EGDI); fixed effects